A Study on Injection Moulding and Injection Blow Molding Technology - Sokkalingam, Rajalingam (Curtin, Sarawak, 2009)
Injection moulding and blow moulding are probably the most widely used process for manufacturing parts by using plastic materials. A wide variety of products are manufactured by using these two technologies, which vary greatly in their size, complexity, and application. The injection moulding process requires the use of an injection moulding machine, raw plastic material and a mould. The process cycle for injection moulding consists of the following four stages: clamping, injection, cooling and ejection. Blow moulding is a manufacturing process that is used to create hollow plastic parts by inflating a heated plastic tube until it fills a mould and forms the desired shape. The manufacturing process is divided into three stages: injection, blowing and ejection. There are many types of materials that may be used in the injection moulding and blow moulding process. Most polymers may be used, including all thermoplastics, some thermosets, and some elastomers.Injection moulding industry is used to create many things such as milk cartons, packaging, bottle caps, automotive dashboards, pocket combs, and most other plastic products available today. Parts made from blow moulding are plastic, hollow, and thin-walled, such as bottles and containers that are available in a variety of shapes and sizes. These study is about the process, equipments, materials and applications involve injection moulding and blow moulding technology. At the same time it’s also discuss about the advantage and disadvantage of both manufacturing technology.